ISARIC-COVID-19 dataset: A Prospective, standardized, global dataset of patients hospitalized with COVID-19 - KORTEN, VOLKAN (My University, 2022)
© The Author(s) 2022.The International Severe Acute Respiratory and Emerging Infection Consortium (ISARIC) COVID-19 dataset is one of the largest international databases of prospectively collected clinical data on people hospitalized with COVID-19. This dataset was compiled during the COVID-19 pandemic by a network of hospitals that collect data using the ISARIC-World Health Organization Clinical Characterization Protocol and data tools. The database includes data from more than 705,000 patients, collected in more than 60 countries and 1,500 centres worldwide. Patient data are available from acute hospital admissions with COVID-19 and outpatient follow-ups. The data include signs and symptoms, pre-existing comorbidities, vital signs, chronic and acute treatments, complications, dates of hospitalization and discharge, mortality, viral strains, vaccination status, and other data. Here, we present the dataset characteristics, explain its architecture and how to gain access, and provide tools to facilitate its use.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Eğitim; Bilgisayar Bilimleri; Bilgi Güvenliği ve Güvenilirliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Library Sciences; Education; Computer Sciences; Information Security and Reliability; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Sosyal Bilimler (SOC); Bilgisayar Bilimi; Matematik; Sosyal Bilimler Genel; BİLGİSAYAR BİLİMİ, BİLGİ SİSTEMLERİ; İSTATİSTİK & OLASILIK; EĞİTİM VE EĞİTİM ARAŞTIRMASI; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Social Sciences (SOC); COMPUTER SCIENCE; MATHEMATICS; SOCIAL SCIENCES, GENERAL; COMPUTER SCIENCE, INFORMATION SYSTEMS; STATISTICS & PROBABILITY; EDUCATION & EDUCATIONAL RESEARCH; INFORMATION SCIENCE & LIBRARY SCIENCE; İstatistik ve Olasılık; Fizik Bilimleri; Bilgi sistemi; Sosyal Bilimler ve Beşeri Bilimler; Bilgisayar Bilimi Uygulamaları; İstatistik, Olasılık ve Belirsizlik; Kütüphane ve Bilgi Bilimleri; Statistics and Probability; Physical Sciences; Information Systems; Social Sciences & Humanities; Computer Science Applications; Statistics, Probability and Uncertainty; Library and Information Sciences